THERAPEUTIC RESPONSE IN PATIENTS WITH CD30+ LYMPHOMAS TO BIOLOGICAL THERAPY - Cakic, Jelena; Đunić, Irena (Medicinski podmladak, 2020)
Introduction: Improvements in combined chemotherapy and radiotherapy of the newly diagnosed Hodgkin's lymphoma (HL) resulted in sustained remission rates of approximately 60% to 80%. However, about 5% of the early stages of the disease and 30% to 40% of advanced disease experience relapses after initial chemiotherapy. Standard in the treatment of patients with relapse or refractory HL is salvage therapy followed by autologous stem cell transplantation (ASCT). In approximately 50% patients relapse after ASCT and then effective therapeutic options are limited.  Brentuximab vedotin (Adcetris®) is a new antibody-drug conjugate that leads to a high response in the CD30 + lymphomas after ASCT.Material and methods: Retrospective study included 20 patients, on average aged 53,31 years, that were diagnosed with Hodgkin and Non-Nodgkin lymphomas and treated with Brentuximab vedotin in Clinic for Hematology, Clinical Center of Serbia, in period of 2002  to 2018y. The informations of the patients were gathered and  databases have been formed from the history of the disease. Statistical analisis included descriptive statistical methods that were done in SPSS programe.Results: The objective response rate (CR + PR) was 76,5% with 29.4% complete remissions (CR) and 47.1% partial remissions (PR). Progressive disease was observed in 17,6%. The median duration of the therapeutic response was 9 months.Conclusion: The application of biological therapy has led to significant progression in the treatment of relapse/refractory Hodgkin's lymphoma, but it is more effective to apply it as a consolidative therapy after ASCT in order to achieve better results of treatment of these patients.Key words: Hodgkin lymphoma, Brentuximab vedotin, treatment efficacy
Keywords: Hodgkin lymphoma, Brentuximab vedotin, treatment efficacy